Electrochemical quinuclidine-mediated Minisci-type acylation of N-heterocycles with aldehydes - Li, Yongmei; Sun, Liangbo; Huang, Shengyang; Xu, Kun; Zeng, Cheng-Chu (Chemical communications (Cambridge, England), 2024)
The electro-generation of acyl radicals from both aromatic and aliphatic aldehydes remains an unmet challenge. We provide a solution to this challenge by merging electro-oxidation and a quinuclidine-mediated hydrogen atom transfer strategy. The generation of acyl radicals at decreased applied potentials compared to that of formyl oxidation exhibits excellent functional group compatibility. The electro-generation of acyl radicals from both aromatic and aliphatic aldehydes is a synthetic challenge. We addressed this challenge by merging electro-oxidation and a quinuclidine-mediated HAT strategy.